Imágenes… ¿sagradas?: negociaciones en torno a lo numinoso en el Aikido del Gran Buenos Aires = Sacred images? : negotiations around the numinous in the Aikido of Greater Buenos Aires - López, Alejandro (Ciencias sociales y religión, 2018)
This paper analyzes the negotiations that take place in Aikido practice spaces located in Greater Buenos Aires around bowing before the photo of Ō-Sensei Morihei Ueshiba, founder of this Japanese martial art. Given the strongly non-verbal character of the practice of Aikido, we focus on the way in which the experiences and meanings of this act are constructed in the space of practice. For this we place these practices in the context of the social imaginaries that frame them. We also discuss the ways in which Aikido has considered the links between martial practice and the world of non-human powers in the context of its internationalization process.